1990
DOI: 10.1088/0029-5515/30/4/010
|View full text |Cite
|
Sign up to set email alerts
|

Radial profiles of hard X-ray emission during steady state current drive in the TRIAM-1M tokamak

Abstract: The hard X-ray emission from the TRIAM-1M tokamak plasma during steady state lower hybrid current drive with a discharge duration of a few minutes was measured with sodium iodide scintillation spectrometers. The radial profiles of the X-ray emission were also measured and indicate that, in the low density regime (ne = (1−3)×1012 cm−3), the current carrying high energy electrons are mainly in the inner region of the plasma column and their radial profile remains unchanged during current drive. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Since TRIAM-1M tokamak has been dismantled, plasma and LH wave parameters for the simulations have been rebuilt from data in Refs. [27,45].…”
Section: Triam-1m Tokamakmentioning
confidence: 99%
See 1 more Smart Citation
“…Since TRIAM-1M tokamak has been dismantled, plasma and LH wave parameters for the simulations have been rebuilt from data in Refs. [27,45].…”
Section: Triam-1m Tokamakmentioning
confidence: 99%
“…Finally, the measured FEB at photon energy k = 60 keV is centrally peaked and fairly broad as shown in Refs. [27,45]. Using HXR diagnostic characteristics given in Ref.…”
Section: Triam-1m Tokamakmentioning
confidence: 99%
“…1. The electron density n e is measured by a microwave interferometer at 140 GHz, the electron temperature T e is measured by a Si(Li) detector [7] and the perpendicular hard X ray temperature profile, T HX (R), is measured by a NaI scintillator array viewing vertically [8].…”
Section: Hit Dischargementioning
confidence: 99%
“…Within these density and ∆R windows the sensitivity of ∆φ was studied. It was found that the HIT transition occurs from 90 • to 120 • , corresponding to the region in which the current drive efficiency is high [8].…”
Section: Onset Conditionsmentioning
confidence: 99%
See 1 more Smart Citation